2009
DOI: 10.1007/s00044-009-9262-0
|View full text |Cite
|
Sign up to set email alerts
|

QSAR analysis of some novel sulfonamides incorporating 1,3,5-triazine derivatives as carbonic anhydrase inhibitors

Abstract: A QSAR study on a series of sulfonamides incorporating 1,3,5-triazine derivatives was performed to explore the physicochemical parameters responsible for their inhibitory activity of carbonic anhydrase I (CA-I) inhibitors. Physicochemical parameters were calculated using WIN CAChe 6.1. Stepwise multiple linear regression analysis was carried out to derive QSAR models, which were further evaluated for statistical significance and predictive power by internal and external validation. The best QSAR model was sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29] Numerous drug design studies have been reported for search of novel compounds. [30][31][32][33][34][35][36][37][38] Numbers of novel drug delivery systems have been utilizes for effective drug delivery. [39][40][41][42][43][44][45][46][47][48] Several agents being used for COVID-19 are under clinical trial and few of them are available in market for sale.…”
Section: Treatment Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29] Numerous drug design studies have been reported for search of novel compounds. [30][31][32][33][34][35][36][37][38] Numbers of novel drug delivery systems have been utilizes for effective drug delivery. [39][40][41][42][43][44][45][46][47][48] Several agents being used for COVID-19 are under clinical trial and few of them are available in market for sale.…”
Section: Treatment Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Recent research has shown that several CA isozymes are drug targets for cancer and infective diseases. There are 11 active CA isozymes known in human [116,117]. Tumour-associated CAs are recognized as hCA IX and hCA XII (also hCA XIV).…”
Section: 3 5-triazine Derivatives Targeting Hca IX and Hca Xiimentioning
confidence: 99%
“…The structures of the 72 compounds used in this study, are given in Table 1. Generation of the Common Pharmacophore Hypotheses (CPHs): Pharmacophore modelling provides a qualitative picture of the geometry of the active site by identifying the chemical features for binding of ligands and their spatial arrangements in 3D space 12 . PHASE module of Schrodinger software 13 was used to generate 3D Pharmacophore models and QSAR studies for the present series of compounds.…”
Section: Datamentioning
confidence: 99%